2017
DOI: 10.1515/hukin-2017-0105
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Hamstring Muscle Activation During two Injury Prevention Exercises

Abstract: The aim of this study was to perform an electromyographic and kinetic comparison of two commonly used hamstring eccentric strengthening exercises: Nordic Curl and Ball Leg Curl. After determining the maximum isometric voluntary contraction of the knee flexors, ten female athletes performed 3 repetitions of both the Nordic Curl and Ball Leg Curl, while knee angular displacement and electromyografic activity of the biceps femoris and semitendinosus were monitored. No significant differences were found between bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 26 publications
3
20
0
1
Order By: Relevance
“…Despite no differences in BF activation between groups, higher levels of BF muscle activation were found at the more flexed (90-30º epoch) compared to the 30-0º epoch (Figure 2). These results agree with Iga et al (2012) and Monajati et al (2017) who demonstrated maximal muscle activity as occurring between 90-30º and 60-40º of knee flexion, respectively. 29,30 Our findings further support the effectiveness of the NHE to elicit high levels of muscle activation (96-114%) during the exercise's first 60º of knee excursion, which falls to and moderate levels of activation (57-75%) during the terminal 30º at long muscle lengths.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Despite no differences in BF activation between groups, higher levels of BF muscle activation were found at the more flexed (90-30º epoch) compared to the 30-0º epoch (Figure 2). These results agree with Iga et al (2012) and Monajati et al (2017) who demonstrated maximal muscle activity as occurring between 90-30º and 60-40º of knee flexion, respectively. 29,30 Our findings further support the effectiveness of the NHE to elicit high levels of muscle activation (96-114%) during the exercise's first 60º of knee excursion, which falls to and moderate levels of activation (57-75%) during the terminal 30º at long muscle lengths.…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with Iga et al (2012) and Monajati et al (2017) who demonstrated maximal muscle activity as occurring between 90-30º and 60-40º of knee flexion, respectively. 29,30 Our findings further support the effectiveness of the NHE to elicit high levels of muscle activation (96-114%) during the exercise's first 60º of knee excursion, which falls to and moderate levels of activation (57-75%) during the terminal 30º at long muscle lengths. 31 Previous research suggests that in the presence of reduced BF activation following injury, changes in the relative contribution of other muscle synergists may represent a compensatory mechanism against neuromuscular inhibition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lower limb movement analysis has been studies to determine the sequence of contraction of posterior and anterior muscles of the thigh [1]. Moreover, muscle force characterization is increasingly important in rehabilitation and sports medicine 4].…”
Section: ; Dinabang; Hamstring; Knee; Normal Values; Physical Therapy;mentioning
confidence: 99%
“…Lower limb movement analysis has been addressed in several studies to determine the sequence of contraction of posterior and anterior muscles of the thigh [1] muscle force characterization is increasingly important in rehabilitation and sports m [2], especially for elite athletes [3, injuries occur during sports when the athlete, during terminal swing phase of running [5] extends the lower limb beyond limits. Rehabilitation is very important after injuries or surgical repair.…”
Section: Introductionmentioning
confidence: 99%